Bone Regeneration Using Porous Titanium Particles versus Bovine Hydroxyapatite: A Sinus Lift Study in Rabbits. (4th August 2011) - Lambert, France; Lecloux, Geoffrey; Léonard, Angelique; Sourice, Sophie; Layrolle, Pierre; Rompen, Eric
ABSTRACT: Aim: The first objective of this study was to qualitatively and quantitatively assess the bone formation process, particularly the long‐term behavior and three‐dimensional volume stability of subsinusal bone regeneration, using titanium (Ti) or bovine hydroxyapatite (BHA) granules, in a rabbit model. The second objective was to evaluate the effect of the hydration of the BHA particles with a therapeutic concentration of doxycycline solution on the osteogenesis and biomaterial resorption. Materials and Methods: Rabbits underwent a double sinus lift procedure using one of three materials: grade 1 porous Ti particles, BHA, or BHA hydrated with doxycycline solution (0.1 mg/ml) (BHATTC). Animals were sacrificed after 1 week, 5 weeks, or 6 months. Samples were analyzed using µCT and nondecalcified histology. Results: The materials used in each of the three groups allowed an optimal bone formation; bone quantities and densities were not statistically different between the three groups. At 6 months, more stable three‐dimensional volume stability was found with Ti and BHATTC ( p = .0033). At 5 weeks and 6 months, bone to material contact corroborating osteoconduction was significantly higher with BHA and BHATTC than with Ti ( p < .0001). Conclusions and Clinical Implications: Even though the studied biomaterials displayed different architectures, they are relevant candidates for sinus lift bone augmentation prior to dental implants because they allow adequate three‐dimensional stability and osteogenesis. However, to recommend the clinical use of Ti, both an observation on the drilling effects of Ti particles and clinical trials are needed.